2016
DOI: 10.1016/j.neuroscience.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Synergies in the space of control variables within the equilibrium-point hypothesis

Abstract: We use an approach rooted in the recent theory of synergies to analyze possible co-variation between two hypothetical control variables involved in finger force production based in the equilibrium-point hypothesis. These control variables are the referent coordinate (R) and apparent stiffness (C) of the finger. We tested a hypothesis that inter-trial co-variation in the {R; C} space during repeated, accurate force production trials stabilizes the fingertip force. This was expected to correspond to a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 44 publications
0
73
0
Order By: Relevance
“…The drift in performance, e.g., in F TOT , suggests a drift at the highest level of the hierarchy, at which F TOT results from a combination of two commands reflected in RC and k (apparent stiffness) defined for a virtual finger (VF, an imagined digit with the same resultant force as all the actual digits combined, Arbib et al 1975). A recent study has shown large intertrial variations in RC and k that kept variance of F TOT very low (Ambike et al 2016b). During the slow F TOT drift, a larger drift is expected within the UCM for F TOT in the {RC; k} space compared with the drift in ORT.…”
Section: Direction Of Force Drift In An Abundant Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…The drift in performance, e.g., in F TOT , suggests a drift at the highest level of the hierarchy, at which F TOT results from a combination of two commands reflected in RC and k (apparent stiffness) defined for a virtual finger (VF, an imagined digit with the same resultant force as all the actual digits combined, Arbib et al 1975). A recent study has shown large intertrial variations in RC and k that kept variance of F TOT very low (Ambike et al 2016b). During the slow F TOT drift, a larger drift is expected within the UCM for F TOT in the {RC; k} space compared with the drift in ORT.…”
Section: Direction Of Force Drift In An Abundant Systemmentioning
confidence: 95%
“…Comparably fast force drifts were also observed in multifinger accurate force production tasks when fingers were perturbed using an "inverse piano" apparatus (Reschechtko et al 2014;Wilhelm et al 2013). To explore drifts in both RC and k, one would have to apply perturbations to the fingers as it was done in a recent study (Ambike et al 2016b), but this may by itself accelerate the drift process. This method remains to be refined if it is to be used in a future study.…”
Section: Origins Of Unintentional Change In Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, they may be measured in different units at the level of performance: R is a referent spatial coordinate that the effector would approach in the absence of external constraints, while C is the apparent stiffness of the effector (see Latash 2010; Ambike et al 2016b). We recently explored inter-trial variation in R and C during constant force production by a finger under continuous visual feedback and found large inter-trial variance in both variables (called R FT and C FT ; FT = fingertip) associated with a low variance in total force (Ambike et al 2016b). In other words, R and C variation was primarily confined to the UCM for the required level of output force.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we explored the unintentional force drift phenomenon using the same method of {R FT ; C FT } estimation as in the previous study (Ambike et al 2016b). Our main hypothesis was that the slow drift in fingertip force after visual feedback removal would be associated with drifts in both R FT and C FT variables along the corresponding UCM as well as orthogonal to it.…”
Section: Introductionmentioning
confidence: 99%